1994
DOI: 10.1084/jem.179.6.1895
|View full text |Cite
|
Sign up to set email alerts
|

The macrophage is an important and previously unrecognized source of macrophage migration inhibitory factor.

Abstract: SummaryFor over 25 years, the cytokine known as macrophage migration inhibitory factor (MIF) has been considered to be a product of activated T lymphocytes. We recently identified the murine homolog of human MIF as a protein secreted by the pituitary in response to endotoxin administration. In the course of these studies, we also detected MIF in acute sera obtained from endotoxin-treated, T cdl-defident (nude), and hypophysectomized mice, suggesting that still more cell types produce MIE Here, we report that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
842
5
11

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 930 publications
(878 citation statements)
references
References 34 publications
20
842
5
11
Order By: Relevance
“…12,13 It has been shown that T cells and macrophages secrete MIF in response to various proinflammatory stimuli such as endotoxins. 4 It is evident that the mechanisms of hair follicle dysfunction in AA are immunological and controlled by activated T cells. 14 Hair loss is associated with a perifollicular lymphocytic infiltrate made up primarily of CD4 þ cells, along with a CD8 þ intrafollicular infiltrate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…12,13 It has been shown that T cells and macrophages secrete MIF in response to various proinflammatory stimuli such as endotoxins. 4 It is evident that the mechanisms of hair follicle dysfunction in AA are immunological and controlled by activated T cells. 14 Hair loss is associated with a perifollicular lymphocytic infiltrate made up primarily of CD4 þ cells, along with a CD8 þ intrafollicular infiltrate.…”
Section: Discussionmentioning
confidence: 99%
“…17 MIF is upregulated by TNF-a, and MIF in turn augments the secretion TNF-a. 4,23 Therefore, these inflammatory cytokines may be implicated in the induction or continuation of damage to hair follicles, and MIF may play an important part in the pathophysiology of inflammatory hair loss as in AA. The MIF gene maps to chromosome 22q11.2, and an SNP (G to C transition) in the 5 0 -flanking region at position 173 of the MIF gene is associated with susceptibility to adult inflammatory arthritis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…mRNA levels were normalized to glyceraldehyde-3-phosphate dehydrogenase (GAPDH) mRNA levels. The above protocol was described previously [10,11]. Three independent experiments with triplicates were performed in each experiment; the results were expressed as mean ± 95% CI.…”
Section: Suppression Of Mif-induced Inflammatory Cytokine Releasementioning
confidence: 99%
“…While macrophages are the major source of MIF, MIF is also produced in pancreatic beta cells, adipocytes, liver, Leydig cells and ovarian follicular cells. When released in response to proinflammatory stimuli MIF inhibits random migration of macrophages and enhances macrophage functions and cytokine production [2]. Recently, it has been shown that MIF and insulin co-localize within the secretory granules of pancreatic beta cells [3].…”
mentioning
confidence: 99%